Methodological support for professional development of university instructors - Polina G. Labzina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Professional development of university instructors has always been an important aspect of the educational environment, which requires appropriate methodological support. It is aimed at creating conditions for improving educational activities and transforming it in accordance with advanced achievements in scientific, practical, and innovative fields. This is necessary to improve the quality of professional training of teaching staff. The content of methodological support is considered in several directions, including active use of innovative technologies in the educational process, development of theoretical foundations for forming creative potential of teaching staff, and assistance in mastering competencies in accordance with the Federal State Educational Standards. This study focuses on the discipline of Academic Writing and creating conditions for professional development of instructors who teach this discipline, since organizing conferences, seminars, and workshops for academic writing instructors and providing opportunities for professional development in this area do not always meet the demand and growing interest in this aspect. The experience of creating and participating in a reading group for one year is presented. The main goal of the group was to develop participants understanding of the concept of academic writing as well as to discuss effective teaching methods for this discipline in higher education institutions. Various pedagogical theories and concepts of academic writing, a critical evaluation of existing writing teaching practices in Russian universities were also considered. The process of the group work, its results, and the advantages and disadvantages of this form of interaction for professional development were described. In conclusion, the reading group is proposed as an opportunity for foreign language instructors not only as a form of methodological support for continuous professional development but also as an opportunity for collaboration in the educational environment of the university.